Helicobacter pylori infection and associated factors - Júlia Silveira Vianna; Ivy Bastos Ramis; Lande Vieira da Silva Junior; Priscila Cristina Bartolomeu Halicki; Thaisa Bozzetti Gauterio; Andrea Von Groll; Pedro Eduardo Almeida da Silva; Carolina Alicia Coch Gioia (Universidade de Santa Cruz do Sul, 2019)
Background and Objectives: Helicobacter pylori is linked to gastroduodenal pathologies. To determine the frequency and potential risk factors of the H. pylori infection. Material and methods: A cross-sectional study was conducted, including 227 patients, submitted to upper gastrointestinal endoscopy. A questionnaire was applied to the patients, before endoscopy. The biopsy specimens were obtained from the antrum and gastric body for histology and PCR. The chi-square test was used for the categorical data analysis. P-values0.05). However, we observed a significant association between the number of persons per household and presence of H. pylori (p=0.04). A statistically significant relation also was found between H. pylori and the patient's age (p=0.04) and between the histological and endoscopic diagnoses and the H. pylori infection (p≤0.01). Conclusions: We found a significant relation between household crowding and presence of H. pylori, which seems facilitate the person-to-person transmission H. pylori within families. Our results also suggest a cohort phenomenon. The increase in the frequency of H. pylori infection according to age may be due the acquisition of bacterium predominantly in childhood, when the sanitary conditions were deficient, and not during adulthood. Once acquired and untreated, the persistent H. pylori infection might have led to the development of severe gastroduodenal diseases.